(untitled) (Hekima Review, 2006)
The notion of the Way is very important in almost all the cultures in the world. Whether it is used in the material sense asthe route, or the path or in the moral and religious sense as the code of conduct or the norm of life, the Way determines in one sense or another the goal and the destiny of people. Considering the actual situation of Africa, the question would probably be: where is the true way for Africans’ fulfilment? How can we reach that way? “Who is it”? A careful reading of the Gospel of John seems to give ananswer to these questions. Unlike the Synoptics, the Johannine Jesus talks mostly about himself with the specific aim to bring the disciples and the opponents, who are the Jews, to believe in him in order to have eternal life through him.